Driving to drink: Tax avoidance along the Washington-Oregon border - K. LoPiccalo (University of California, Economics Department, 2016)
This paper uses store-level data on consumer liquor revenues and volume sales in Oregon to estimate the effect of state tax differentials on consumer demand. Liquor privatization in Washington led to higher prices from new taxes. I calculate the impact of tax incidence on tax avoidance using variation in store proximity to the Washington-Oregon (WA-OR) border. By calculating driving distances between Oregon liquor stores and border crossings, I find that stores closest to the WA-OR border experienced an additional 20 percent increase in revenues relative to interior stores, and that avoidance behavior dissipates monotonically from the Washington-Oregon state line.
Keywords: D40; H20; H21; H22; H26; L10; 330; Tax avoidance; tax incidence; cross-border shopping; alcohol